The Pharmacological actions of Plants of the Genera Cotyledon and Crassula, N.O. Crassulaceae, with other Papers - Sapeika, Norman (Division of Clinical Pharmacology, 2020)
The disease known as "Krimpsiekte" (Nenta, Kraamsiekte, cerebrospinal meningitis, Cotyledonosis) has been recognised in South Africa for ma.ny years. It appears in arid parts of the Cape Province, and affects animals which have ingested certain members of the genus Cotyledon (N.O. Crassulaceae).